Determining the angle of femoral torsion and association with shaft length and mid circumference - Yadav, Subodh Kumar; Singh, Sanjenbam Arun Chandra; Yadav, Renu (Asian Journal of Medical Sciences, 2020)
Background: Angle of femoral torsion has an anatomical variation based on sex, geography, ethnicity and occupation and concludes various impact factor on determining the angulation as well as the length of the bone. Aims and Objective: Thus, present study is aimed to determine the angle of femoral torsion in Nepalese population. Materials and Methods: This is a cross-sectional study carried out at the Department of Anatomy, Nobel Medical College and Teaching Hospital, Biratnagar, Nepal. Of the total 60, unpaired and unknown gender, dry femora were collected during one year period and separated as right sided (n=30) and left sided (n=30) according to the standard anatomical landmarks. Measurement of angle was done by Kingsley Olmsted method and the length, mid-circumference by measuring tape. Results: The angle of torsion in dry femora (n=60) for right (16.73± 3.095) and left (16.67± 2.963) side were recorded. The mean shaft length, mid circumference for right sided femora were recorded as 39.367±0.9185 and 7.933 ± 0.6661cm respectively. The mean shaft length and mid circumference were 38.917± 0.8914 and 7.933 ± 0.5833cm respectively for left sided femora. Differences (ATF, p=0.932, LF, P=0.059, MCF, P=1) of variables between right and left femora were analyzed and correlation of angle of femoral torsion with shaft length and midshaft circumference (ATF vs MCF, p= 0.571 and LF, p=0.153) was done. Conclusion: Documenting the femoral angle of torsion with shaft length, midshaft circumference in normal dry femora of cadaver is of great importance for Orthopedic surgeons since it provides a knowledge for planning the hip surgeries.